1999
DOI: 10.1016/s1074-5521(99)80066-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis and specificity in enzymatic glycoside hydrolysis: a 2,5B conformation for the glycosyl-enzyme intermediate revealed by the structure of the Bacillus agaradhaerens family 11 xylanase

Abstract: The 2,5B conformation found for the alpha-linked xylobiosyl-enzyme intermediate of Xyl11, unlike the 4C1 chair conformation observed for other systems, is consistent with the stereochemical constraints required of the oxocarbenium-ion-like transition state. Comparison of the Xyl11 covalent glycosyl-enzyme intermediate with the equivalent structure for the related family 12 endoglucanase, CelB, from Streptomyces lividans reveals the likely determinants for substrate specificity in this clan of glycoside hydrola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
121
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 39 publications
6
121
0
Order By: Relevance
“…Recently the structure of an inactive mutant of the Xyn11 from Bacillus agaradhaerens in complex with xylotriose has been obtained (17). The interactions are very similar to that described at subsites Ϫ2 and Ϫ1 for the covalent intermediate complex (16), with the addition of the interactions for the Ϫ3 subsite.…”
Section: Production and Structural Properties Of The Xylanase Vari-mentioning
confidence: 71%
See 4 more Smart Citations
“…Recently the structure of an inactive mutant of the Xyn11 from Bacillus agaradhaerens in complex with xylotriose has been obtained (17). The interactions are very similar to that described at subsites Ϫ2 and Ϫ1 for the covalent intermediate complex (16), with the addition of the interactions for the Ϫ3 subsite.…”
Section: Production and Structural Properties Of The Xylanase Vari-mentioning
confidence: 71%
“…5, structural alignment of the above xylanases with that of A. niger enzyme showed that four of the A. niger xylanase variants (Y10A, Y89A, Y164A, and W172A) have been mutated at positions corresponding to residues that have been involved in discrete subsites of other family 11 xylanases. Tyr 10 corresponds to Trp Xyn11 , all involved in stacking interaction with the xylose ring in substite Ϫ2 of these xylanases (13,16,17,22,26 XYNII , which are thought to determine subsites ϩ1 and ϩ2 of XYNI and XYNII enzyme, respectively (22). Moreover, the oxygen atom OH of residue Tyr 6 is in the same position as atom Glu…”
Section: Production and Structural Properties Of The Xylanase Vari-mentioning
confidence: 99%
See 3 more Smart Citations